Vorstellungen von DaF-Lehramtsstudierenden über den qualitativ hochwertigen DaF-Unterricht - Retelj, Andreja (Vestnik za tuje jezike, 2024)
The issues of what constitutes high-quality teaching and how this can be guaranteed are the subject of intense debate among both general and specialized didacticians. In practice, however, the under-standing of the concept of teaching quality is too often left to individual interpretations and beliefs. The main aim of this article is to determine the perceptions of the quality of German language teach-ing (GFL) among students at the beginning of their master’s degree programme in German. The study is based on the analysis of students’ drawings, which depict their perceptions of the quality of the teacher’s work, student activities, and the learning environment. The results indicate that most student teachers still imagine high-quality teaching in a traditional manner, with the teacher at the forefront, a large whiteboard, students sitting in rows, solving tasks, and listening to the teacher’s instructions and explanations. The image of the classroom as a closed room with a teacher’s desk, student desks, and teaching aids remains firmly anchored in their perceptions. Although there are signs of change – as some pre-service teachers have presented active working methods, collaborative learning, modern technologies and learning materials, as well as alternative classroom arrangements – there is a need for pedagogical and methodological courses to address topics that may seem trivial at first glance but are, in fact, crucial. To improve the quality of school practice, student teachers should be encouraged to reflect on the quality of teaching and supported in their initial teacher steps during their studies.
Keywords: bodoče učiteljice in učitelji; drawings; German as a foreign language; kakovost pouka; nemščina kot tuji jezik; prepričanja učiteljic in učiteljev; quality; risbe; student teachers; teacher beliefs